How Indigenous Peoples Respond to the Mandatory Vaccination Policy on COVID-19 - Pratiwi, Hersa Endah; Firman, Firman (Jurnal Kebijakan Kesehatan Indonesia, 2023)
Background: The crisis of the COVID-19 outbreak which claimed millions of human lives has prompted various responses from the global community. The COVID-19 Vaccination Policy is one of the Indonesian government's breakthroughs in responding to the outbreak crisis. This is regulated in Kepres No. 14, 2021 years which regulates the obligation of vaccines for every Indonesian citizen, including sanctions for refusing. The process of implementing this rule faces pros and cons among indigenous peoples. One of the main causes is the unmanaged public communication from the government, so that the information that reaches the public tends to be confusing. In the end, this triggered a negative response from the indigenous community, which even tended to strongly oppose vaccination policies that were considered to have a negative impact on health, including threats of administrative sanctions and fines imposed on individuals and communities who refused vaccines. The purpose of this study was to examine the perceptions of the Bayan Traditional Village community towards the mandatory COVID-19 vaccination policy. Research Methods: A qualitative study using an ethnographic design, that focuses on assessing perceptions according to values and socio-culture of the indigenous people of Bayan, North Lombok, regarding the mandatory COVID-19 vaccination policy. Sampling was carried out purposively, with a total of 29 informants from the category of stakeholder groups, women's groups, youth groups, traditional leaders, village heads, and heads of health centers. The sampling technique was FGD (focus group discussions) according to the distribution of informants. Results: Indigenous Peoples consider that the mandatory COVID-19 vaccination policy is a government program that needs to be supported by the community to prevent and reduce transmission of COVID-19. Although, indigenous peoples also admit that they are more afraid of administrative sanctions such as delays in social assistance such as the BLT/ PKH Programs, and including following appeals from traditional leaders, and the COVID-19 task force. In other words, indigenous peoples do not object to the obligation to vaccinate, but they also believe that there is a right and opportunity to postpone and wait for non-participation for reasons that they are still healthy, will not travel, and are not yet a priority. Conclusion: The Task Force and Puskesmas officers have a strategic function to provide complete education and information to indigenous peoples, and the involvement of traditional leaders is very effective in increasing community participation, at best minimizing the potential for negative responses or community rejection of the obligation to vaccinate.